Pengaruh Smartphone Addiction Terhadap Bedtime Procrastination Taruna Poltekip Angkatan 56 Prodi Manajemen Pemasyarakatan - Novita Nur Marlesa; Padmono Wibowo (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
The general public must continually be informed of technological developments, such as the use of smartphones, also referred to as "smarphones," in order to be able to complete this role. Large-scale touchscreen cellphones have already been adopted by several countries throughout the world. Additionally, this phenomena was noticed by Cadets from the Polytechnic for Criminal Justice, notably Class 56 for the Correctional Management Study Program. However, there may be certain drawbacks to utilizing a smartphone. The taruna's most obvious practical effect, which resulted in time-wasting tiredness, was a brilliant addiction phone, The researcher did research to comprehend the relationship between the smartphone's kecanduan and the prokrastination of sleep time in the 56th program study of management of the POLTEKIP. This study employs quantitative methods to assess the effects of the independent and dependent variables. The study sample consists of 31 cadets from batch 56 of the POLTEKIP Correctional Management Study Program. The distribution of surveys through Google Forms was done using the random sample data collection technique. Because of the strong association between the variables X and Y revealed by the study's findings, the alternate hypothesis (Ha) was accepted and the null hypothesis was rejected. The study also reveals a weak relationship between procrastinating before bed and smartphone addiction.